Serum selenium, copper and zinc concentrations in inhabitants of S. Miguel Island (Azores Archipelago) - Viegas-Crespo, Ana Maria (2014)
Abstract(2386) de Comunicação oral apresentada em "17th International Congress of Biochemistry and Molecular Biology" e "1997 Annual Meeting of the American Society for Biochemistry and Molecular Biology", August 24-29, 1997 San Francisco, California, USA.